Responses of dioecious Populus to heavy metals: a meta-analysis - Lei Yu; Shuanglei Tang; Jieyu Kang; Helena Korpelainen; Chunyang Li (Forestry Research, 2023)
A total of 946 sets of comparative data were collected from 20 publications and a meta-analysis performed to evaluate the responses of growth, photosynthetic capacity, oxidative stress and antioxidants in Populus females and males under exposure to heavy metals, like Cu, Mn, Zn, Pb and Cd. It was found that heavy metals have negative effects on Populus growth and photosynthetic capacity, as the average total biomass, leaf biomass, stem biomass, root biomass and height decreased by 29.78%, 33.41%, 27.22%, 35.30% and 34.83%, respectively. Furthermore, total chl, Pn, gs, E, Ci decreased by 23.30%, 26.03%, 40.49%, 23.76% and 18.24%, respectively. In addition, heavy metals increased oxidative stress and antioxidant enzyme activities: the average values of TBARS, H2O2, \begin{document}${\text{O}^-_2} $\end{document} and MDA increased by 51.39%, 55.79%, 64.67% and 48.92%, respectively, and proline, APX, NPT, POD, CAT and SOD increased by 68.91%, 64.81%, 68.40%, 57.34%, 77.30% and 49.01%, respectively. However, there were sex-specific responses to heavy metals: females suffered more negative effects, as they had significantly greater decreases in root biomass, R/S ratio, height and total chl, and significantly smaller increases in NPT and POD activities than males. The present meta-analysis shows the responses of Populus females and males to heavy metals on a regional scale, which is crucial for understanding the patterns of sexual dimorphism and sex ratio biases in Populus with increasing heavy metal pollution in the future.